Characterization of natural zeolite for adsorptive removal of antibiotics from aqueous solution - Lye, Jimmy Wei Ping (2014)
The persistent existence of antibiotics in sewage wastewater treatment plants in recent years has emerged as a serious concern. In this study, natural zeolite (NZ02) obtained from China was employed as an adsorbent to remove tetracycline (TC) from aqueous solution. The characterization results show that the NZ02 consists of quartz, clinoptilolite-Na and heulandite having the CEC of 62.18cmol/kg and the surface area of 36.646m2/g. Adsorption results show that the maximum adsorption capacity of TC on NZ02 was 19.30mg/g and the equilibrium data followed theLangmuir adsorption isotherm model.